Intelligent prediction of lower extremity loadings during badminton lunge footwork in a lab-simulated court - Nur Ikhwan Mohamad (Tanjung Malim, 2023)
Intelligent prediction of lower extremity loadings during badminton lunge footwork in a lab-simulated court by Nur Ikhwan Mohamad